49th Winter School on Wave and Quantum Acoustics XLVIIIth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, February 24–27, 2020 - Bismor, Dariusz (Archives of Acoustics, 2020)
49th Winter School on Wave and Quantum Acoustics constituted platforms for sharing the results and achievements obtained in different branches of physical acoustics, as molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state, acoustic emission, and others. Moreover, researches in some selected topics related to those mentioned above (e.g. optoelectronics, relaxation processes) were presented during the school.The conference consisted of the 16th Workshop on Acoustoelectronics and the 16th Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods. However, the organizers are opened to organizing workshops on other subjects in future. We would like to invite scientific centers and other professional groups to cooperate in organizing workshops on the subjects of their interests. XLVIIIth Winter School on Environmental Acoustics and Vibroacoustics was a forum for all environmental and vibroacoustics fields. Particularly it was concerned with traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems. During the Conference, seminars on “Measurement of noise and vibration at the workplace” and Environmental noise monitoring”, combined with measurement workshops, were organised in association with SVANTEK. The Conferences began with the special, joined session dedicated to celebration of the 15th Jubilee Conference Integrated Optics – Sensors, Sensing Structures and Methods. In summary, 48 people participated in Conferences and seminars, presenting 37 lectures, reports and posters. In this issue one can find abstracts of some lectures and posters, which were presented during the Conferences.